(3TQM eNJUQ CHj LYaQ GdWMGhis - (3YdGA GdOjf Hf eMeO Hf ESeGYjd Hf ESMGb GdSeQbfOi GdESHjLGHis; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s ((3eMeO Hf ehSi Hf CQGd GdMQV s)
(3ChdgG (B:s
(3jHJOA ef CKfGA GdebOeI s
(3BNQgG (B:s
(3CKfGA cJGH GdMLQ s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B107s
Keywords: (3Gdabg GdMfajs